Introducing Computer Adaptive Testing to a Cohort of Mathematics Teachers: The Case of Concerto - S. Kanageswari Suppiah Shanmugam; Leong Chee Kin (Southeast Asian Mathematics Education Journal, 2012)
This article describes a study that explores on-line assessment, with the objectives to identify features that support or impede the usability of Concerto, an on-line adaptive testing software that was developed by the Psychometrics Centre of the University of Cambridge. We report on the analysis of data collected during a one-month in-service programme organised for secondary teachers and teacher educators from the Southeast Asian Minister of Education Organisation (SEAMEO) region. The study identifies the challenges the participants encountered during a one-day workshop and evaluates thedifficulties of adopting Concerto to create a simple and an adaptive on-line mathematics test. While the small study limits the possibility of applicability for other samples, yet the findings of the study illustrate the complexity of using the Concerto’s features and the commonly occurring difficulties, providing the basis for the development of some new workshop materials that will contribute to the improvement of introductory Concerto workshops that will be conducted in the future.